Assessing the consistency of iPSC and animal models in cystic fibrosis modelling: A meta-analysis. - Toqa Darwish; Azhar Al-Khulaifi; Menatalla Ali; Rana Mowafy; Abdelilah Arredouani; Suhail A Doi; Mohamed M Emara (PLoS ONE, 2022)
Introduction Cystic fibrosis (CF) is a hereditary autosomal recessive disorder caused by a range of mutations in the CF Transmembrane Conductance Regulator (CFTR) gene. This gene encodes the CFTR protein, which acts as a chloride channel activated by cyclic AMP (cAMP). This meta-analysis aimed to compare the responsiveness of induced pluripotent stem cells (iPSCs) to cAMP analogues to that of commonly used animal models. Methods Databases searched included PubMed, Scopus, and Medline from inception to January 2020. A total of 8 and 3 studies, respectively, for animal models and iPSCs, were analyzed. Studies were extracted for investigating cAMP-stimulated anion transport by measuring the short circuit current (Isc) of chloride channels in different animal models and iPSC systems We utilized an inverse variance heterogeneity model for synthesis. Results Our analysis showed considerable heterogeneity in the mean Isc value in both animal models and iPSCs studies (compared to their WT counterparts), and both suffer from variable responsiveness based on the nature of the underlying model. There was no clear advantage of one over the other. Conclusions Studies on both animal and iPSCs models generated considerable heterogeneity. Given the potential of iPSC-derived models to study different diseases, we recommend paying more attention to developing reproducible models of iPSC as it has potential if adequately developed.